Kolaborasi Stakeholder Dalam Peningkatan Karakter Disiplin Di Sekolah - Dzakir, Ahmad; Nahdi, Khirjan; Juaini, Muhamad (Universitas Hamzanwadi, 2024)
The aim of this research is First, Description and analysis of teacher and student collaboration in Improving Discipline Character at Darul Mujahidin Plus Tahfiz Islamic Elementary School. Second, description and analysis of collaboration between teachers and parents in improving discipline character at Darul Mujahidin Islamic elementary School. Third, description and analysis of collaboration between teachers, students and parents in improving discipline character at Darul Mujahidin Islamic elementary School. In this research, researchers used a qualitative approach. Data collection was carried out using unstructured interviews, observation and documentation. The research informants were the chairman of the foundation, deputy principal, teachers, students and parents at the Plus Tahfiz Darul Mujahidin Islamic Elementary School. After the data is obtained, it is then analyzed, while the steps for processing qualitative descriptive data are by means of data reduction, data display, conclusions and data verification. In this research the researcher found several findings (1) Teacher and Student Collaboration in Improving Discipline Character in Elementary Schools (2) Teacher and Parent Collaboration in Improving Discipline Character in Elementary Schools school committees, communication, home visits and student parent meetings and teachers (GROUP). (3) Collaboration between Teachers, Students and Parents in Improving Discipline Character in Elementary Schools through counseling guidance, home visits, and through contact books.